Determinación de Listeria spp. mediante PCR en Tiempo Real en muestras de leche cruda, recolectadas en la provincia de Pichincha. - Cabrera Rodríguez, María Alexandra (2016)
This research is based on the application of the Real Time Polymerase Chain Reaction (PCR) to determine the presence of Listeria genus in raw milk. In Ecuador, especially in the province of Pichincha, studies on these bacteria are scarce and practically nonexistent in raw milk. Milk production is one of the main livestock activities in the province, which is why the study of this product is essential. Being all cantons of this province, milk producers, three of them were randomly selected to collect samples which are Cayambe, Quito and Pedro Moncayo. The application of the technique of Real Time PCR in the detection of microorganisms and especially bacteria in food is based on three fundamental aspects: its sensitivity, specificity and ability to process large quantities of samples, it is possible to detect small amounts of pathogens, which is not possible with conventional methods, is why it is ideal for detecting Listeria spp. in raw milk. In this study, one positive of a total of 60 samples was determined, representing 1.6% of Listeria spp. in raw milk from three farms of Pichincha. These results, according to the statistical analysis performed with Kruskal – Wallis test, show that the bacteria is present in raw milk but not in representative quantities.